Regional variability in the atmospheric nitrogen deposition signal and its transfer to the sediment record in Greenland lakes - Anderson, N.J.; Curtis, C.J.; Whiteford, E.J.; Jones, V.J.; McGowan, S.; Simpson, G.L.; Kaiser, J. (Wiley, 2018)
Disruption of the nitrogen cycle is a major component of global environmental change. d15N in lake sediments is increasingly used as a measure of reactive nitrogen input but problematically, the characteristic depleted d15N signal is not recorded at all sites. We used a regionally replicated sampling strategy along a precipitation and N-deposition gradient in SW Greenland to assess the factors determining the strength of d15N signal in lake sediment cores. Analyses of snowpack N and d15N-NO3 and water chemistry were coupled with bulk sediment d15N. Study sites cover a gradient of snowpack d15N (ice sheet: 26&; coast 210&), atmospheric N deposition (ice sheet margin: _ 0.2 kg ha21 yr21; coast: 0.4 kg ha21 yr21) and limnology. Three 210Pb-dated sediment cores from coastal lakes showed a decline in d15N of ca. 21& from _ 1860, reflecting the strongly depleted d15N of snowpack N, lower in-lake total N (TN) concentration (_ 300 lg N L21) and a higher TN-load. Coastal lakes have 3.7–7.13 more snowpack input of nitrate than inland sites, while for total deposition the values are 1.7–3.63 greater for lake and whole catchment deposition. At inland sites and lakes close to the ice-sheet margin, a lower atmospheric N deposition rate and larger in-lake TN pool resulted in greater reliance on N-fixation and recycling (mean sediment d15N is 0.5–2.5& in most inland lakes; n56). The primary control of the transfer of the atmospheric d15N deposition signal to lake sediments is the magnitude of external N inputs relative to the in-lake N-pool.